The Premorbid Adjustment Scale as a measure of developmental compromise in patients with schizophrenia and their healthy siblings - Shapiro, D.I.; Marenco, S.; Spoor, E.H.; Egan, M.F.; Weinberger, D.R.; Gold, J.M. (Schizophrenia research, 2009)
Schizophrenia is associated with subtle developmental compromise, but the degree to which this is also associated with heritability and genetic risk is uncertain. The goal of the current study was to investigate the childhood, adolescent, and early adulthood social and academic function of patients with schizophrenia, their healthy siblings, and normal controls, using the Premorbid Adjustment Scale (PAS). Generalized Estimating Equations were conducted to account for nesting of subjects within families. Patients ( N = 286) scored significantly worse than their healthy siblings ( N = 315) at every age period; siblings scored significantly worse than controls ( N = 261) at every age period. In probands, PAS scores got worse after early adolescence while control and proband scores improved after late adolescence. Furthermore, patient PAS scores significantly predicted the scores of their own discordant siblings in childhood and late adolescence. This effect approached significance in early adolescence and in the general scale. Thus, the most premorbidly impaired patients tended to have non-ill siblings with worse premorbid adjustment scores than the siblings of less impaired probands. The results suggest that both patients and many of their siblings share poor adjustment in childhood and adolescence, possibly due to shared genetic or environmental risk factors.